Prevalence of obesity and body weight perception among pregnant women - Rachael Shamini Danasamy,; Leelavathi Muthupalaniappen, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Obesity is rapidly increasing worldwide and there is a general misconception regarding body weight perception. The aim of this study was to determine the prevalence of obesity and body weight perception among pregnant women. A total of 315 pregnant women participated in this study. Their Body Mass Index (BMI) was recorded and weight perception was assessed using a questionnaire. About two third (60.6%, n=191) participants in the study had excess weight out of which, 29.8% (n=94) were obese and 30.8% (n=97) were overweight. There was poor agreement between participant’s true body weight category and their perception (k=0.185 (95% CI, 0.119 to 0.258), p<0.001). Majority of participants who were obese (84%, n=79) and overweight (77.4%, n=75) underestimated their weight status. Only a very small percentage of obese (16%, n=15) and overweight 18.6% (n=18) participants had correct perception of their weight. However, the majority (84.3%, n=86) of participants with normal body weight had correct perception regarding their body weight. This study found that most obese and overweight women tend to underestimate their weight status while those of normal weight had correct perception of their body weight. The inaccurate perception of those who are obese and overweight may impact weight gain during pregnancy and affect pregnancy related complications. Education regarding ideal body weight and its benefits needs to be instilled during pre-pregnancy care to achieve better overall outcome.